Integrating Minangkabau Cultural Elements in Educational Games: A Mix-Methods Study for Science Learning Engagement - Zakirman, Zakirman; Widiasih, Widiasih; Pandiangan, Paken; Aprianti, Rika; Nadiyyah, Khoirotun; Wahyudi, Ricky; Handayani, Raden Sumratul (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – Science learning often struggles to boost student engagement and understanding. Educational games offer an innovative approach, but they often overlook local cultural contexts, reducing their relevance for students. This study examines the views of science educators on the use of Edu Game Adventure based on Minangkabau culture in science learning.Method – This study uses a mixed-method approach with questionnaires distributed to 50 science teachers and lecturers in West Sumatra. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative analysis focused on open-ended responses. The purposive sampling ensures diverse perspectives on the integration of local cultures in science learning, providing a deeper understanding of practitioners' views across different educational levels and experiences.Findings – The results indicate that most practitioners view the integration of Minangkabau culture in educational games positively. 80% believe it boosts student interest in science, 75% say it promotes cultural diversity and local values, 65% feel it encourages active involvement, and 70% think it broadens perspectives on cultural diversity. These findings suggest that integrating Minangkabau culture enhances student engagement and understanding, providing valuable insights for designing culturally relevant learning tools. Research Implications – The study's results offer practical guidance for curriculum developers and educators to integrate local culture into engaging, meaningful learning designs, highlighting the importance of culturally relevant content to enhance teaching effectiveness.